Failure diagnosis of the steam generator based on improved BP network and Particle - Qi Fujun; Niu Qingsong; Peng Jing; Tian Zhiguang (E3S Web of Conferences, 2021)
In order to overcome the problems of slow rate of convergence and falling easily into local minimum in BP algorithm, this paper introduces the adaptive particle swarm optimization algorithm and combining model. The paper applies it to steam turbine-generators fault diagnosis. The experiment data shows that the algorithm converges quickly and recognizes faults efficiently; it has a reference value for faults diagnosis.